Holistic needs assessment in outpatient cancer care: a randomised controlled trial - Stefano Schipani; Craig White; Marie-Thérèse Lussier; Austyn Snowden; Jenny Young; Esther Murray; Claude Richard; Denis Roberge (BMJ Open, 2023)
Design Analyst blinded, parallel, multi-centre, randomised controlled trial (RCT).Participants People with confirmed diagnoses of cancer (head and neck, skin or colorectal) attending follow-up consultation 3 months post-treatment between 2015 and 2020.Intervention Holistic needs assessment (HNA) or care as usual during consultation.Objective To establish whether incorporating HNA into consultations would increase patient participation, shared decision making and postconsultation self-efficacy.Outcome measures Patient participation in the consultations examined was measured using (a) dialogue ratio (DR) and (b) the proportion of consultation initiated by patient. Shared decision making was measured with CollaboRATE and self-efficacy with Lorig Scale. Consultations were audio recorded and timed.Randomisation Block randomisation.Blinding Audio recording analyst was blinded to study group.Results 147 patients were randomised: 74 control versus 73 intervention.Outcome No statistically significant differences were found between groups for DR, patient initiative, self-efficacy or shared decision making. Consultations were on average 1 min 46 s longer in the HNA group (respectively, 17 m 25 s vs 15 min 39 s).Conclusion HNA did not change the amount of conversation initiated by the patient or the level of dialogue within the consultation. HNA did not change patient sense of collaboration or feelings of self-efficacy afterwards. HNA group raised more concerns and proportionally more emotional concerns, although their consultations took longer than treatment as usual.Implications for practice This is the first RCT to test HNA in medically led outpatient settings. Results showed no difference in the way the consultations were structured or received. There is wider evidence to support the roll out of HNA as part of a proactive, multidisciplinary process, but this study did not support medical colleagues facilitating it.Trial registration number NCT02274701.